Advances in Evaporated Solid-Phase-Crystallized Poly-Si Thin-Film Solar Cells on Glass (EVA). (11th January 2009) - Kunz, O.; Ouyang, Z.; Wong, J.; Aberle, A. G.
Abstract : Polycrystalline silicon thin-film solar cells on glass obtained by solid-phase crystallization (SPC) of PECVD-deposited a-Si precursor diodes are capable of producing large-area devices with respectable photovoltaic efficiency. This has not yet been shown for equivalent devices made from evaporated Si precursor diodes ("EVA" solar cells). We demonstrate that there are two main problems for the metallization of EVA solar cells: (i) shunting of the p-n junction when the air-side metal contact is deposited; (ii) formation of the glass-side contact with low contact resistance and without shunting. We present a working metallization scheme and first current-voltage and quantum efficiency results of 2 cm 2 EVA solar cells. The best planar EVA solar cells produced so far achieved fill factors up to 64%, series resistance values in the range of 4-5 Ω cm 2, short-circuit current densities of up to 15.6 mA/cm 2, and efficiencies of up to 4.25%. Using numerical device simulation, a diffusion length of about 4 μ m is demonstrated for such devices. These promising results confirm that the device fabrication scheme presented in this paper is well suited for the metallization of EVA solar cells and that the electronic properties of evaporated SPC poly-Si materials are sufficient for PV applications.